A perfect multi-hop teleportation scheme for transfer of five-qubit entangled states using intermediate nodes. Issue 12 (12th July 2018) - Choudhury, Binayak S.; Samanta, Soumen
Abstract: In this paper, we consider a multi-hop teleportation protocol for transfer of certain five-qubit entangled states. The speciality of this protocol is that intermediate nodes between the sender and the receiver are introduced. Teleportation processes over long distances are problematic because of the existence of the environmental noise which is almost unavoidable and adversely affects the entangled quantum channel. With a view to the above, intermediate nodes are introduced which are connected in series by entanglement. These short range quantum channels minimize the risk of the protocol being affected by noise. The present protocol is performed in an integrated manner in which the parties in the intermediate nodes act independently. A remarkable feature of the protocol is that only 3.13% of the basis elements are involved in the measurements. We also calculate the efficiency and indicate the advantages of the present protocol. The work is in the direction of research for transferring entangled quantum states.